PENDIDIKAN DALAM PERSPEKTIF IBNU KHALDUN - YAYAT HIDAYAT (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2019)
Abstract : Ibn Khaldun is one of the leaders of Islamic thinkers who has a great influence in the development of science. Ibn Khaldun is better known as a historian and social expert. As stated in his Muqoddimah work, besides having the concept of education in an educational perspective is the result of the ideas of Ibn Khaldun who emphasized education. Ibn Khaldun's view of education rests on concepts and philosophical-empirical approaches. Through this approach, he provides direction to the vision of the ideal and practical goals of Islamic education. Based on the results of research from the literature that has been done that Ibn Khaldun is a great figure in the Islamic world, who succeeded in contributing so much in the scientific world that exists in the world. The thoughts of Ibn Khaldun cannot be separated from the roots of Islamic thought. Ibn Khaldun considers that education is the essence of human existence. Ibn Khaldun argues that education seeks to give birth to a cultured society and strives to preserve the future existence of society. Ibn Khaldun's view of education rests on concepts and philosophical-empirical approaches. Through this approach, he provides direction to the vision of the ideal and practical goals of Islamic education. The challenge of education according to Ibn Khaldun is that education can create quality human resources, namely giving birth to a culture of society and trying to preserve and increase the existence of the next society.Keywords: Education, Ibnu Khaldun, Perspective